Nanomaterials safety : toxicity and health hazards - Ghosh, Shyamasree (De Gruyter, 2019)
This monograph summarizes the current knowledge on potential health hazards induced by nanomaterials from different sources and sort such as food, drugs and silver nanoparticles. Methods to assess toxicity as well as known effects on the genome, neuronal and respiratory system are discussed. Besides the impact on human and animal life the books also addresses aquatic toxicity.
Keywords: Nanostructured materials -- Toxicology.; Nanostructured materials -- Health aspects.; Nanostructures -- adverse effects; Nanostructures -- toxicity; Safety; Nanomatériaux -- Toxicologie.